Analysis of Knowledge and Ability of Building Construction Workers on Attitudes on Work Accident Risk - Maddeppungeng, Andi; Ujianto, Rifky; Setiawati, Dwi Novi; Intari, Dwi Esti; Asyiah, Siti; Enjelina, Ella (JURUSAN TEKNIK SIPIL, 2024)
Construction work, especially building construction, has a high risk of work accidents, because it involves many elements. Now in building construction projects, the importance of knowledge about K3 and the ability of workers has become a basic need. Attitudes towards occupational safety also have an important role, because they can reflect the level of attention a person has to work safety aspects. The purpose of this study is to determine and analyze whether the knowledge and ability of building construction workers affect attitudes on accident risk. The approach applied is an associative approach. The population in this study is individuals involved in building construction, with the total population obtained is 44 respondents. Data is collected through the use of online questionnaires through the Google Form platform. After that, the data was analyzed using SEM-PLS 4.0 software. The results showed that there was a positive and significant influence between workers' knowledge of attitudes with a path coefficient value of 0.348. There is a positive and significant influence between the ability of workers to attitudes with a path coefficient value of 0.484. There is a moderate influence between workers' knowledge and ability on attitudes, as evidenced by the R2 value obtained 0.598.